2012
DOI: 10.1002/asia.201200725
|View full text |Cite
|
Sign up to set email alerts
|

Control of Circularly Polarized Luminescence by Using Open‐ and Closed‐Type Binaphthyl Derivatives with the Same Axial Chirality

Abstract: The solution-dispersed-state and polymer-dispersed-state circular dichroism (CD) and circularly polarized luminescence (CPL) properties of chiral binaphthyl fluorophores could be controlled by the choice of open- or closed-type substituents on the binaphthyl units and by the axial chirality of the binaphthyls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
44
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 117 publications
(51 citation statements)
references
References 42 publications
6
44
0
1
Order By: Relevance
“…Theresults indicated that the average molar ratio between chiral emitters and Hmim is 0.015 in both R-ZIF and S-ZIF.Under UV irradiation, R-ZIF exhibited bright blue emission in the solid state ( Figure 2a). [15] This chirality inversion was further confirmed by CPL measurements (Figure 2d and Figure S2 c, d). Absorption spectra showed that there was no obvious change in R-ZIF compared to R-1, which indicated that there was no severe aggregation of the chiral emitters on the skeleton of ZIF-8 ( Figure 2b).…”
supporting
confidence: 62%
See 1 more Smart Citation
“…Theresults indicated that the average molar ratio between chiral emitters and Hmim is 0.015 in both R-ZIF and S-ZIF.Under UV irradiation, R-ZIF exhibited bright blue emission in the solid state ( Figure 2a). [15] This chirality inversion was further confirmed by CPL measurements (Figure 2d and Figure S2 c, d). Absorption spectra showed that there was no obvious change in R-ZIF compared to R-1, which indicated that there was no severe aggregation of the chiral emitters on the skeleton of ZIF-8 ( Figure 2b).…”
supporting
confidence: 62%
“…The CD spectrum of R-1 located around 375 nm (S 0 -S 1 transition) showed apositive Cotton effect while anegative Cotton effect was found for R-ZIF.The chirality inversion can be explained by the dihedral angle (q)c hange of the axially chiral compounds.T he change of the dihedral angle would lead to an inversion of the chirality. [15] This chirality inversion was further confirmed by CPL measurements (Figure 2d and Figure S2 c, d).…”
supporting
confidence: 62%
“…In the ground state, conversely, the predicted first ECD band is always positive for (a R )‐ 2 a along a large portion of the torsional energy curve, in particular that comprised between and including the two minima (Supporting Information, Figure S3). A pronounced dependence of CPL on the aryl–aryl torsion has been reported for other biaryls, for example 1,1′‐binaphthyl derivatives . In these cases, however, the observed CPL bands are allied with weak transitions of the naphthalene 1 L b ‐type, and do not belong to the main exciton couplet between naphthalene 1 B b ‐type transitions, in contrast with BODIPY DYEmers.…”
Section: Resultsmentioning
confidence: 72%
“…In particular, it was interesting to study the CPL behavior of compounds, which showed the peculiar exciton‐coupled ECD spectra discussed above. In fact, bis‐chromophoric exciton‐coupled compounds have been studied systematically only in the related context of fluorescence‐detected circular dichroism (FDCD), whereas covalent exciton‐coupled systems have been considered only occasionally in CPL measurements . On the contrary, there is much interest in CPL as a means for the detection and characterization of chiral supramolecular aggregates of chromophoric species, which are also exciton‐coupled.…”
Section: Introductionmentioning
confidence: 99%
“…18 Chiral fluorophores 2 and 4 showed clear CPL behaviors with CPL = 438 nm for 2 and 401 nm for 4. Dimensionless Kuhn's anisotropy in the photoexcited state (g em ) is defined by:…”
Section: ¹4mentioning
confidence: 95%